Sobre o modo de relação do surdo com a língua portuguesa escrita - Bizio, Lucimar (2015)
This paper reflects on the relationship between the deaf to the Portuguese language written form. It discusses the relationship among speaking, sign language and writing. The objective is to discuss the complexity of the issue of the writing of deaf people, either to the ones that use sign language to communicate, to the ones who can speak or to the Portuguese teacher to the deaf. The trajectory of this paper involves the way the issue of language acquisition is designed, being it the main theme on the deafness studies including at the pedagogy field, because it is assumed that schooling allows the deaf to join the field of Portuguese writing. I also discuss how the bilingualism to deaf people deals with the relationship between the deaf and sign language and the deaf and Portuguese language. The questioning of such issues led to the need of investigating what mother language to deaf people is. Faced with a particular conception of writing, which includes a theory about the functioning of language, I attach a discussion of written texts by deaf students that aims to overcome the concept of error as a deficit, but that can show the singular, unique presence of a subject in language: taking into account the articulation subject/language/speaking-writing-gesture. The discussion held here was sent from the dialogue with a Linguistics affected by Lacanian psychoanalysis as proposed by the Brazilian Interactionism, developed by Cláudia Lemos (1992, 2002, 2006) and by other researchers affiliated to its proposal and specially by the theoretical developments put forward by the research group Language Acquisition, Pathologies and Clinic, headed by Maria Francisca Lier-DeVitto and Lúcia Maria Guimarães Arantes